The sounds are not alone if we care about their meaning: sensory organ and socio-bio-ecosystemic music - Calabretta, Pietro (Canadian Acoustics, 2024)
A marginal instrument such as the orgue sensoriel (OS), created for disabled people, invites us to interrogate the meaning of musical practices by situating them in their respective contexts of production and reproduction, determined in their material, imaginary and symbolic reality. The eco-logical perspective is chosen for its analytical and descriptive virtues, rather than for its normative implications. In presenting the life and origins of the OS, three concepts exogenous to the field of music are introduced: ecological niche, microbiome and musiculture. As metaphors – figuratively, heuristically and pedagogically rich – they enable the placement of the sounds of OS, and their meaning, in the socio-bio-ecosystems of each (set of) situation(s). Analysts, artists and educators can work creatively and sensitively on those three dimensions to restore complexity and variability to the meaning of musical practices, and to orient new experiences